2007
DOI: 10.1002/jez.b.21208
|View full text |Cite
|
Sign up to set email alerts
|

PCR survey of Xenoturbella bocki Hox genes

Abstract: Xenoturbella bocki has recently been identified as one of the most basal deuterostomes, although an even more basal phylogenetic position cannot be ruled out. Here we report on a polymerase chain reaction survey of partial Hox homeobox sequences of X. bocki. Surprisingly, we did not find evidence for more than five Hox genes, one clear labial/PG1 ortholog, one posterior gene most similar to the PG9/10 genes of Ambulacraria, and three central group genes whose precise assignment to a specific paralog group rema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 43 publications
3
16
0
Order By: Relevance
“…Summarizing, and as shown in table 1, we found that, as a general pattern, the number of genes belonging to each family is lower in S. roscoffensis than in X. bocki: 18 bHLHs and 225 GPCRs were present in the former; 33 bHLHs and 258 GPCRs in the latter. This is consistent with, for instance, the number of Hox genes detected: three in acoels [66]; five in xenoturbellids [77]. Here, the complexity of the different families (we refer to the total number of genes per family plus the number of subfamilies present) in these two species is not directly related to the apparent structural complexity of acoel and Xenoturbella neural architectures.…”
Section: A Genomics View Of Xenacoelomorpha Neurogenesissupporting
confidence: 83%
“…Summarizing, and as shown in table 1, we found that, as a general pattern, the number of genes belonging to each family is lower in S. roscoffensis than in X. bocki: 18 bHLHs and 225 GPCRs were present in the former; 33 bHLHs and 258 GPCRs in the latter. This is consistent with, for instance, the number of Hox genes detected: three in acoels [66]; five in xenoturbellids [77]. Here, the complexity of the different families (we refer to the total number of genes per family plus the number of subfamilies present) in these two species is not directly related to the apparent structural complexity of acoel and Xenoturbella neural architectures.…”
Section: A Genomics View Of Xenacoelomorpha Neurogenesissupporting
confidence: 83%
“…The provisional conclusion is that ophiuroids have a cluster with Hox1 and Hox3 in the anterior class, Hox7 and Hox8 plus at least one other gene in the medial class, and several genes in the posterior class. The GenBank data were also cited by Fritzsch et al [66] in support of the contention that Hox4 was absent in ophiuroids. However, these data are in reference to expression of genes during regeneration of Amphiura filiformis - this is very different from saying that Hox4 is absent from the ophiuroid cluster because there is no reason to assume that Hox4 must reveal its presence during regeneration.…”
Section: Resultssupporting
confidence: 67%
“…2004; Hejnol and Martindale 2009; Moreno et al. 2009) while four Hox genes have been reported from X. bocki (Fritzsch et al. 2008; Thomas-Chollier and Martinez 2016).…”
Section: Discussionmentioning
confidence: 99%